PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERASI: (Studi Pada Perumda Air Minum Kabupaten Lamongan) - Diah Rohmatus Sholikhah; Yulie Wahyu Ningsih; Rizky Wahyudha Rosiawan (ANALISA : JURNAL MANAJEMEN DAN AKUNTANSI, 2026)
This study aims to analyze the effect of the work environment and work discipline on employee performance with work motivation as a moderating variable at Perumda Air Minum Kabupaten Lamongan. A quantitative approach was employed using saturated sampling involving 96 employees. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The findings indicate that the work environment and work discipline have a positive and significant effect on employee performance. However, work motivation has no significant direct effect on employee performance. Furthermore, work motivation positively moderates the relationship between the work environment and employee performance, while it weakens the relationship between work discipline and employee performance. These findings imply that improving the quality of the work environment and implementing consistent work discipline are essential to enhance employee performance. This study contributes to the development of human resource management by providing empirical evidence regarding the moderating role of work motivation in improving employee performance within a regional public water utility